Friction and rolling–sliding wear of DC-pulsed plasma nitrided AISI 410 martensitic stainless steel - Corengia, P. (2006)
In the present work, industrial-scale DC-pulsed plasma nitriding for 20 h at 673K was used to improve the wear resistance of an AISI 410 martensitic stainless steel. The tribological behaviour was studied and compared to the behaviour of the same steel in as-received condition.   Pin-on-disc dry tests, using an alumina ball as counter-body, were carried out to determine the evolution of the friction coefficient. The wear resistance was investigated using an Amsler-disc-machine, employing a dry combined contact of rolling–sliding with three different applied loads. The wear mechanisms involved during rolling–sliding of unnitrided and plasma nitrided steels were investigated by microscopic observation of the surfaces, the corresponding cross-sections and the produced wear debris. The combination of different wear mechanisms taking place in the wear process of unnitrided and nitrided materials were discussed and analyzed. In contrast to the unnitrided steel, DC-pulsed plasma nitrided samples presented an improvement in the friction coefficient and the wear rate.